2014
DOI: 10.3892/ijmm.2014.1794
|View full text |Cite
|
Sign up to set email alerts
|

Tougu Xiaotong capsule promotes chondrocyte autophagy by regulating the Atg12/LC3 conjugation systems

Abstract: Abstract. We have previously reported that Tougu Xiaotong capsule (TXC) inhibits tidemark replication and cartilage degradation by regulating chondrocyte autophagy in vivo. Autophagy, a cell protective mechanism for maintaining cellular homeostasis, has been shown to be a constitutively active and protective process for chondrocyte survival. However, it remains unclear whether TXC promotes chondrocyte autophagy by regulating the autophagy-related (Atg)12/microtubuleassociated protein 1 light chain 3 (LC3) conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Drugs regulating other targets, such as Tougu Xiaotong Capsule, facilitate autophagy by balancing ATG12/LC3 coupling system (Li et al, 2014). Several autophagosome formation indexes including ATG3, ATG7, ATG12-5 and BECN1 in trehalose treated chondrocytes and the proportion of LC3-II:LC3-I increased as the dose of the drug increases, and the level of SQSTM1 decreased, indicating that trehalose can enhance autophagy flux (Tang et al, 2017).…”
Section: Status Of Oa Therapeutics Targeting Autophagy Signaling Pathwaymentioning
confidence: 99%
“…Drugs regulating other targets, such as Tougu Xiaotong Capsule, facilitate autophagy by balancing ATG12/LC3 coupling system (Li et al, 2014). Several autophagosome formation indexes including ATG3, ATG7, ATG12-5 and BECN1 in trehalose treated chondrocytes and the proportion of LC3-II:LC3-I increased as the dose of the drug increases, and the level of SQSTM1 decreased, indicating that trehalose can enhance autophagy flux (Tang et al, 2017).…”
Section: Status Of Oa Therapeutics Targeting Autophagy Signaling Pathwaymentioning
confidence: 99%
“…Moreover several autophagy-inducing agents are object of recent researches as protective for OA. Among them, Tougu Xiaotong capsule inhibits tidemark replication and cartilage degradation by regulating chondrocyte autophagy and it could be a potential therapeutic agent for the reduction of cartilage degradation that occurs in osteoarthritis [ 77 ]. Manipulation of Hypoxia-inducible factor 1-alpha (HIF-1α) and 2-alpha (HIF-2α) has been suggested as a promising approach to the treatment of OA.…”
Section: Autophagymentioning
confidence: 99%
“…Another study showed that Du-Huo-Ji-Sheng decoction (a KTBAM compound) exerted significant therapeutic effects in osteoarthritic rabbits, probably through inhibiting the expression of VEGF and hypoxia-inducible factor-1 α [15]. Yaotongning capsules (a KTBAM compound) promoted proliferation and glycosaminoglycan synthesis in IL-1 β -induced chondrocytes and may have potential activity in treating chondrocyte degeneration caused by osteoarthritis [69, 70]. A study has found that kidney-tonifying and blood-activating Chinese herbs may suppress the expression of interferon regulatory factor 7 (IRF-7) by regulating the TLR4/MyD88 signaling pathway, resulting in less secretion of interleukin 6 (IL-6) and matrix metallopeptidase 13 (MMP-13), which alleviates inflammation and delays cartilage destruction [71].…”
Section: Discussionmentioning
confidence: 99%